SOSIALISASI 6 (ENAM) LANGKAH MENCUCI TANGAN PADA ANAK DI MI AL-BADARIAH DESA TATAH LAYAP PADA MASA PANDEMI COVID-19 - Noor Aisyah; Ahmad Irawan; Gilang Ramadhan; Sigit Giantoro (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Washing hands as often as possible and in the 6 (six) steps of washing hands in children is one of the most important steps to prevent Covid-19 infection in children. Washing hands with soap is much more effective in killing germs, bacteria and viruses than washing hands with water alone. Soap can easily destroy the lipid membrane of Covid-19, rendering the Covid-19 virus inactive. The purpose of this activity is to increase knowledge of elementary school students, in the socialization of 6 (six) steps to wash hands for elementary school children during the Covid-19 pandemic at MI Al-Badariah, Tatah Layap Village. The activities carried out were in the form of health education about hand washing in 6 (six) steps, the benefits of washing hands, and demonstrations about washing hands in 6 steps by elementary school students grades 1-6 at MI Al-Badariah. The activity has been carried out on December 2, 2021, from 08.00 to 12.00 WIB. The results of community service were obtained by increasing children's knowledge regarding the 6 (six) steps of proper hand washing.